2015
DOI: 10.1155/2015/150673
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Association between Polymorphisms of the TLR4 Gene and Infection with the Hepatitis B and C Viruses

Abstract: Toll-like receptor 4 (TLR4) plays a crucial role in the early recognition of pathogenic microorganisms and provides an ideal model to investigate the consequences of genetic variation and susceptibility to diseases. The present study investigated the occurrence of the single nucleotide polymorphisms (SNPs) rs4986790 (A>G) and rs4986791 (C>T) in the TLR4 gene in chronic carriers of the hepatitis B (HBV) and C (HCV) viruses. A total of 420 blood samples were collected (HBV, 49; HCV, 72; and controls, 299) at the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
1
6
0
Order By: Relevance
“…When microorganisms in the body are infected, the host Toll-like receptor 4 (TLR4) can be activated and expressed in different immune cells, such as neutrophils, monocytes, macrophages, and dendritic cells, which generate inflammatory mediators and induce a variety of inflammatory processes [ 23 , 24 ]. In the early inflammatory stage, procalcitonin is secreted by cytokine-activated macrophages and interacts with epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When microorganisms in the body are infected, the host Toll-like receptor 4 (TLR4) can be activated and expressed in different immune cells, such as neutrophils, monocytes, macrophages, and dendritic cells, which generate inflammatory mediators and induce a variety of inflammatory processes [ 23 , 24 ]. In the early inflammatory stage, procalcitonin is secreted by cytokine-activated macrophages and interacts with epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, Spearman correlation analysis was applied to analyze the correlation levels of bile acid and serum homocysteine and HE, which were 0.29 and -0.19, respectively. Multivariate logistic regression diagnostic model of bile acid level and serum homocysteine revealed that the AUC value of the ROC curve was 0.7201, indicating macrophages, and dendritic cells, which generate inflammatory mediators and induce a variety of inflammatory processes [23,24]. In the early inflammatory stage, procalcitonin is secreted by cytokine-activated macrophages and interacts with epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…In accord with this finding, Brazilian study negated any frequency or association between TLR4 rs4986791 SNP and susceptibility to HCV burden in its population. 51 However, many reports elaborated the engagement of endogenous ligands (like damage-associated molecular patterns) by TLR4 which triggers downstream signaling, evokes specific transcription factors and finally provokes the expression of interferons among other inflammatory cytokines during HCV infection. 19 , 52 …”
Section: Discussionmentioning
confidence: 99%
“…Thereafter, 134 articles were removed based on those containing unrelated titles, abstracts and full text, resulting in 7 eligible articles. Accordingly, only seven eligible articles were enrolled in this study for quality assessment and meta-analysis ( Figure 1) [17][18][19][20]22,23,34]. Subsequently, quality assessment was performed via NOS and included studies were shown to be of high and moderate quality (Supplemental Table 1).…”
Section: Literature Research and Characteristics Of Included Studiesmentioning
confidence: 99%
“…There are two studies indicating that both rs4986790 and rs4986791 are associated with HCV infection in Saudi Arabia and Pakistan [17,18]. However, these results remain controversial as some other studies could not detect any association [19][20][21]. Moreover, other TLR4 SNPs might play other roles in HCV infection.…”
Section: Introductionmentioning
confidence: 99%